Antiferromagnet-ferromagnet transition in La1–xSrxMn0.5Ni0.5O3 (0 ≤ x ≤ 0.2) ceramics - Troyanchuk, I.O.; Karpinsky, D.V.; Bushinsky, M.V.; Sirenko, V.A.; Sikolenko, V.V.; Franz, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Ceramics samples of La1–xSrxMn0.5Ni0.5O3 (0 ≤ x ≤ 0.2) with perovskite structure have been studied by neutron diffraction method, magnetometry and magnetoresistance measurements. Structural data testify a partial order of the Ni and Mn ions in all the compounds in spite of chemical substitution of the La3+ ions by Sr2+ ones and an increase of the oxidation state of the Ni ions from 2+ towards to 3+ one. Magnetic structure of the compounds changes from ferromagnetic one (specific for the compound with x = 0) to antiferromagnetic (compounds with x ≥ 0.1) while the temperature of a transition into paramagnetic state remains about 270 K for all the samples. Magnetoresistance gradually decreases with temperature increase and strontium content. The results are discussed assuming nearly equal ferromagnetic and antiferromagnetic components of the superexchange interaction Ni2+–O–Mn4+ while the interaction between Ni3+ and Mn4 ions is considered to be strongly antiferromagnetic.